CBX7 regulates stem cell-like properties of gastric cancer cells via p16 and AKT-NF-κB-miR-21 pathways - Su-Jie Ni; Li-Qin Zhao; Xiao-Feng Wang; Zhen-Hua Wu; Rui-Xi Hua; Chun-Hua Wan; Jie-Yun Zhang; Xiao-Wei Zhang; Ming-Zhu Huang; Lu Gan; Hua-Lin Sun; Goberdhan P. Dimri; et al. (Journal of Hematology & Oncology, 2018)
Abstract Background Chromobox protein homolog 7 (CBX7), a member of the polycomb group (PcG) family of proteins, is involved in the regulation of cell proliferation and cancer progression. PcG family members, such as BMI, Mel-18, and EZH2, are integral constituents of the polycomb repressive complexes (PRCs) and have been known to regulate cancer stem cell (CSC) phenotype. However, the role of other PRCs’ constituents such as CBX7 in the regulation of CSC phenotype remains largely elusive. This study was to investigate the role of CBX7 in regulating stem cell-like properties of gastric cancer and the underlying mechanisms. Methods Firstly, the role of CBX7 in regulating stem cell-like properties of gastric cancer was investigated using sphere formation, Western blot, and xenograft tumor assays. Next, RNA interference and ectopic CBX7 expression were employed to determine the impact of CBX7 on the expression of CSC marker proteins and CSC characteristics. The expression of CBX7, its downstream targets, and stem cell markers were analyzed in gastric stem cell spheres, common cancer cells, and gastric cancer tissues. Finally, the pathways by which CBX7 regulates stem cell-like properties of gastric cancer were explored. Results We found that CBX7, a constituent of the polycomb repressive complex 1 (PRC1), plays an important role in maintaining stem cell-like characteristics of gastric cancer cells via the activation of AKT pathway and the downregulation of p16. Spearman rank correlation analysis showed positive correlations among the expression of CBX7 and phospho-AKT (pAKT), stem cell markers OCT-4, and CD133 in gastric cancer tissues. In addition, CBX7 was found to upregulate microRNA-21 (miR-21) via the activation of AKT-NF-κB pathway, and miR-21 contributes to CBX7-mediated CSC characteristics. Conclusions CBX7 positively regulates stem cell-like characteristics of gastric cancer cells by inhibiting p16 and activating AKT-NF-κB-miR-21 pathway.